Rearing and rehabilitation of common seal pups (Phoca vitulina) - Mayer, SJ; Hutchison, AJ (BMJ Publishing Group Ltd, 1990)
Veterinary surgeons may be presented with seal pups that require rearing and rehabilitation. This paper describes the feeding, weight gains and clinical care of 22 harbour or common seal pups (Phoca vitulina) that were reared and rehabilitated at the RSPCA Seal Assessment Unit in Norfolk during 1989. Eighteen of the seals survived and were released but four died. On arrival the pups' mean (+/- sd) bodyweight was 9.2 +/- 2.1 kg; those which survived stayed an average of 14.2 +/- 2.3 weeks before they were released at an average weight of 35.5 +/- 3.5 kg.